Methodological System of Professional Training of Future Physics Teachers in the Process of Teaching the Course “Molecular Physics” - Orazov, Bexultan; Issayeva, Gulnara; Syzdykova, Zhainagul; Nametkulova, Farida (Jurnal Pendidikan IPA Indonesia, 2025)
In the context of digitalizing the educational process for training future physics teachers, enhancing the methodological component of the “Molecular Physics” course in higher education institutions of Kazakhstan is crucial. This study aims to develop and implement a methodological system for the professional training of future physics teachers through the “Molecular Physics” course. The research employs a mixed-methods approach, including both qualitative and quantitative data collection techniques. The study justifies the theoretical need for reorganizing the methodological system and explores the potential benefits of the proposed methodology in enhancing the study of “Molecular Physics” among students in Kazakhstan’s higher education institutions. Data were gathered through pre- and post-tests, surveys, and a controlled experiment involving 162 participants, divided into experimental and control groups. The study outlines pedagogical conditions essential for the successful implementation of this methodology, including developing motivation among future teachers, improving teaching methodologies, and utilizing effective digital technologies. It recommends implementing this methodology through controlled tasks for independent study, employing both traditional and non-traditional teaching methods, organizing various forms of independent student work, establishing a clear scoring system, and providing feedback through innovative assessment methods. The research introduces a structural and content model for professional training that consists of three interrelated components: methodological, content-activity, and criterion-evaluation. The practical value of this work lies in its updated methodological system, which is grounded in practical methods and technologies aimed at improving the study of physics in higher education institutions in Kazakhstan. This approach not only enhances the educational process but also aligns with the evolving demands of digital education.